Quantitative assessment of muscle injury by (23)Na magnetic resonance imaging - Dahlmann, Anke; Kopp, Christoph; Linz, Peter; Seuß, Hannes; Eckardt, Kai-Uwe; Luft, Friedrich C.; Titze, Jens; Uder, Michael; Hammon, Matthias; Cavallaro, Alexander Josef (SpringerPlus, 2016)
(23)Na magnetic resonance imaging ((23)Na-MRI) is able to measure Na(+) in vivo in humans and allows quantification of tissue sodium distribution. We now tested the utility of (23)Na-MRI technique in detecting and assessing sports-related acute muscular injury.We assessed tissue Na(+) of both lower legs with a 3T MRI scanner using a customized (23)Na knee coil. The affected left calf muscle in an injured volleyball player showed a hyperintense Na(+) signal. Follow-up measurements revealed persistently increased muscle Na(+) content despite complete clinical recovery.Our findings suggest that (23)Na-MRI could have utility in detecting subtle muscular injury and might indicate when complete healing has occurred. Furthermore, (23)Na-MRI suggests the presence of substantial injury-related muscle electrolyte shifts that warrant more detailed investigation.
EVALuna2:3865